The potassium nutrition affects the growth and photosynthesis of Lilium cultivated in acidic peat - Barrera-Aguilar, Enoc; Valdez-Aguilar, Luis Alonso; Castillo-González Ana María; Ibarra-Jiménez Luis; Rodríguez- García Raúl; Alia-Tejacal, Iran (Revista Mexicana de Ciencias Agrícolas, 2018)
Lilium (Lilium sp.) is one of the ornamental species with the highest value and is cultivated to produce fresh cut f lowers or potted plants. The incorporation of floriculture to crop technology of crops without soil requires the determination of optimum levels of nutrition for each of the required elements. In the present study, the effect of the K concentration in the nutritive solution was evaluated in order to define the concentration that permits the production of Lilium f lowers to be cultivated in acidic peat. The solutions in the study consisted of four concentrations of K: 0, 5, 10, and 20 mM. Most of the response variables evaluated, allowed us to define an optimal concentration of K as between and 10 mM, an interval that would be the equivalent of the sufficient nutrient levels. The former was observed in parameters like the diameter of the f lower, height of the plant, and total dry weight of the plant. In contrast, excessive levels (20 mM) or deficiencies (0 mM) of K cause a reduction of height and in total dry weight. The increase of the concentration of K in the nutritive solution was related to an increase in the concentration of K in all of the organs, but principally in the root. The greatest net photosynthesis registered in the young leaves was shown with the supplement of 0 to 20 mM of K, which could be because of a process regulation because of lack of carbohydrates as is suggested by less accumulated biomass.